2014
DOI: 10.1007/s13197-014-1552-y
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of mislabeling in meat products using DNA-based assay

Abstract: Considering that the authentication of food contents is one of the most important issues for the food quality sector, and given the increasing demand for transparency in the meat industry followed the horsemeat scandal in Europe, this study investigates processed-meat products from Italian markets and supermarkets using the mitochondrial cytochrome b gene qualitative PCR identification system in order to verify any species substitution or mislabeling. The results revealed a high substitution rate among the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 26 publications
1
54
0
Order By: Relevance
“…Mislabeling of food products has been mentioned as a major public health risk associated with food safety in the food market in 17 of the full-text articles included in this review [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]154]. Mislabeling of food products includes false advertising, deliberately or accidentally leaving out ingredients, not listing potential health effects, and claiming a food contains ingredients that it does not for financial gain with the intent of deceiving the consumer regarding what is actually in the package [155].…”
Section: Sood M 2014 [67] Indonesia Field Inspectionmentioning
confidence: 99%
“…Mislabeling of food products has been mentioned as a major public health risk associated with food safety in the food market in 17 of the full-text articles included in this review [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]154]. Mislabeling of food products includes false advertising, deliberately or accidentally leaving out ingredients, not listing potential health effects, and claiming a food contains ingredients that it does not for financial gain with the intent of deceiving the consumer regarding what is actually in the package [155].…”
Section: Sood M 2014 [67] Indonesia Field Inspectionmentioning
confidence: 99%
“…Amplification was conducted on a cytochrome b gene with a common forward primer and specific reverse primers, as first described previous literature [18]. The size calculated from these samples were different than previously reported [13], whereas bovine samples, a band size of 320 bp was calculated, and from porcine samples a band size of 360 bp was calculated. Based on this study, conventional and isolation kit method showed a 92% PCR amplification from all samples.…”
Section: Pcr Amplification Showed Varied Results Depending On Dna Isomentioning
confidence: 99%
“…The oligonucleotide primers [13], were synthesized by Integrated DNA Technology, Singapore. According to this study [13], oligonucleotides used were forward primer SIM 5'-GAC CTC CCA GCT CCA TCA AAC ATC TCA TCT TGA TGA AA -3', used for both porcine and bovine samples, and a bovine reverse primer 5'-CTA GAA AAG TGT AAG ACC CGT AAT ATA AG -3' and porcine reverse primer 5'-GCT GAT AGT AGA TTT GTG ATG ACC GTA-3'.…”
Section: Dna Amplification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of undeclared species may cause health problems such as food allergy (Naaum et al 2018;Temisak et al 2019) and a fatal neurodegenerative disease caused by bovine spongiform encephalopathy (Sultan et al 2004). The previous studies reviewed that over 50% of processed meat products tested were mislabeled (Cawthorn et al 2013;Di Pinto et al 2015;Quinto et al 2016). Therefore, accurate methods for determination of meat species in food products are required.…”
Section: Introductionmentioning
confidence: 99%